Analysis on the Current Situation and Countermeasures of Family Sex Education for Preschool Children - He, Xiangwei (International Journal of Management and Education in Human Development, 2022)
The Development and progress of society and the improvement of the living standard determine the different speeds and degrees of children’s physical and mental development. Sex Education for children is an aspect that cannot be ignored in the whole education. The family is the primary place for Children’s sexual identification, and family sex education has certain significance and function in children’s development. Family sex education is an important topic in children’s pre-school period, which plays a key role in children’s adolescence, future, and life. Based on the current situation of family sex education for preschool children, this paper analyzes the current situation of family sex education for preschool children.